2010
DOI: 10.1007/s11743-010-1242-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties and Micellar Molecular Interaction in Binary Systems of a Biosurfactant Sodium Deoxycholate (NaDC) with Conventional Surfactants

Abstract: Surface tension for the binary mixtures of a biosurfactant sodium deoxycholate (NaDC) with three different conventional surfactants (p-(1,1,3,3-tetramethylbutyl)phenol polyoxyethylene, polyoxethylene-10-oleyl ether, and sodium oleate) were measured in buffer solutions at different temperatures. Surface properties were determined as well as the micellar characteristics like composition, micellar molecular interaction parameter (b), activity coefficients (f 1 , f 2 ), and the free energy of micellization were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…According to the Eqs (1) and (2), the values of Г max and A min for these mixed systems are calculated and listed in The values of A min decreased with increasing in α NaOL for NaOL/ NaDC and NaOL/AOT systems, which indicated an increased concentration of NaOL on the surface adsorption layer. In our previous studies, for the NaDC/NaOL system in buffer solution (pH 10), the A min values initially increase and then decrease when α NaDC exceeds 0.33 [10] .…”
Section: Molar Ratio Effectmentioning
confidence: 80%
See 1 more Smart Citation
“…According to the Eqs (1) and (2), the values of Г max and A min for these mixed systems are calculated and listed in The values of A min decreased with increasing in α NaOL for NaOL/ NaDC and NaOL/AOT systems, which indicated an increased concentration of NaOL on the surface adsorption layer. In our previous studies, for the NaDC/NaOL system in buffer solution (pH 10), the A min values initially increase and then decrease when α NaDC exceeds 0.33 [10] .…”
Section: Molar Ratio Effectmentioning
confidence: 80%
“…In this case, the surface properties of the mixed surfactants are better than those of the individual ones [9] . The common methods used to study mixed surfactants include surface tension [10] , conductivity [11] , fluorescence [12] , small angle neutron scattering [13] and surface partitioning [14] . In recent years, the researches on NaOL mixtures have expanded in various fields.…”
Section: Introductionmentioning
confidence: 99%
“…The previous investigations of this surfactant revealed that Brij 97 had abundant phase behaviors, and formed various liquid crystals including lamellar, cubic, and hexagonal phases with different additives. [15][16][17] In our recent work, [18] it was found that a strong interaction exists among Brij 97 and NaDC molecules and the mixed micelle formed in this system is quite stable.…”
Section: Introductionmentioning
confidence: 82%
“…2 In our previous studies, Brij97 could form various aggregates including micellar, 3 microemulsion, 4 lamellar, 5 hexagonal 6,7 and cubic 8,9 liquid crystals. Although the formation conditions of various Brij97-based aggregates have been shown clearly, the detailed information of the self-assembled process of Brij97 in the oil-water interface at the nanometer scale 10 is difficult to obtain from experiments.…”
Section: Introductionmentioning
confidence: 96%